Q: How do you factor the equation 2xsquared plus -5x equals 12?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

f(x) = 2x2 + 4x - 7

A quadratic equation.

That's the equation.

You don't factor an equation. You factor an expression.So we'll forget about the "equals 0" for a second, while we factor "x2 plus 5x plus 6".x2 + 5x + 6 = (x + 3) (x + 2).Now, if you want this expression to be equal to zero, that can only happen when 'x' is -2 or -3.

That word "equals" in there makes it an equation.

Related questions

It has roots x = 2.618 and x = 0.38197

OK. That's the equation of a parabola, symmetrical with respect to the x-axis, opening downward, with its nose at y=1. What's the question ?

There is no equation. An equation is true, whereas the statement ( 5 + 7 = -12 ) is false.

f(x) = 2x2 + 4x - 7

It is: 4x squared

A quadratic equation.

2x2-4x-3x+6 2x2-7x+6 (2x+3)(x+2)

Iron plus chlorine equals Iron chloride is the word equation.

That's the equation.

x = 0 and y = 4

cacl2 plus na2s equals cas plus

The summary equation is the formula equation. Sugar equals alcohol plus carbon dioxide. The formula is C6H12O6 which equals 2 CH3CH2OH plus 2 CO2.